2005
DOI: 10.1002/pi.1919
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and properties of hyperbranched poly(amine‐ester) films using acetal cross‐linking units

Abstract: Novel films based on cross-linked hyperbranched poly(amine-ester) (HPAE) were prepared by cross-linking the terminal hydroxyl groups of HPAE using glutaraldehyde (GA). The cross-linking process was monitored by measuring the intrinsic viscosity of HPAE/GA in N,N-dimethylacetamide. The surface structures of the cross-linked HPAE films obtained from different HPAE/GA ratios were imaged using atom force microscopy, and their properties were characterized in terms of hydrophilicity, solvent swelling, mechanics, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 60 publications
1
4
0
Order By: Relevance
“…24 The results of different generation HPAE-OHs were showed in the Table I. It could be clearly seen that with the increase of generation the hydroxyl values were close to theoretical value, which indicated that the structure was apt to regulation.…”
Section: Resultssupporting
confidence: 49%
See 1 more Smart Citation
“…24 The results of different generation HPAE-OHs were showed in the Table I. It could be clearly seen that with the increase of generation the hydroxyl values were close to theoretical value, which indicated that the structure was apt to regulation.…”
Section: Resultssupporting
confidence: 49%
“…24 HPAE-OHs was dissolved in excess benzoic anhydride with imidazole as a catalyst (in pyridine) at 80 C of water bath for 3 hours to acetylate the hydroxyl groups in HPAEOHs. By back-titrating the above mixture with NaOH solution (0.1 mol L…”
Section: Determined the Hydroxyl Values Of Hpae-ohsmentioning
confidence: 99%
“…The small size was probably due to the volume restriction effect of HBPAE micelles. 27) The HRTEM image of TiO 2 NCs showed the unidirectional lattice fringes of the ( 101 3.2 Self-assembly of TiO 2 NCs on the surface of cotton fabric The modification of the surface chemistry of cotton fibers is necessary prior to the assembly of TiO 2 NCs on a cotton surface. A cotton fiber is mainly composed of cellulose with repeating units of 1,4-D-glucopyranose.…”
Section: Synthesis and Characterization Of Hbpae-cappedmentioning
confidence: 99%
“…The hydroxyl values of different generation HPAE-OHs were measured and calculated by the method described in the previous paper [22]. The results of different generation HPAE-OHs were showed in the Table 1.…”
Section: Chemical Structure Of Hpae-ohs and Hpae-co-plamentioning
confidence: 99%
“…The hydroxyl values of HPAE-OHs were determined by the following method [22]. HPAE-OHs was dissolved in excess benzoic anhydride with imidazole as a catalyst (in pyridine) at 80°C of water bath for three hours to acetylate the hydroxyl groups in HPAE-OHs.…”
Section: Determination the Hydroxyl Values Of Hpae-ohsmentioning
confidence: 99%